1970
DOI: 10.1161/01.res.26.4.507
|View full text |Cite
|
Sign up to set email alerts
|

Response of the Rat Aortic Media to Hypertension

Abstract: Clinical and experimental studies indicate that hypertension accelerates the development of arteriosclerosis. Morphological and chemical studies of the distended rat thoracic aorta were undertaken to define the structural and compositional alterations of the media which accompany hypertension and to relate these changes to increases in calculated medial stress. An 8-week period of hypertension was associated with significandy greater diameter, medial thickness, and cross-sectional area of the media of the thor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
150
0
5

Year Published

1983
1983
2007
2007

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 333 publications
(175 citation statements)
references
References 32 publications
20
150
0
5
Order By: Relevance
“…It is now well established that collagen content is increased in hypertension. 10 ' 11 Using the same morphometric methods as in the present study, we reported a similar increase in collagen content in hypertensive rats. 18 '…”
supporting
confidence: 82%
“…It is now well established that collagen content is increased in hypertension. 10 ' 11 Using the same morphometric methods as in the present study, we reported a similar increase in collagen content in hypertensive rats. 18 '…”
supporting
confidence: 82%
“…2 Increased vascular collagen is also found in hypertension and probably contributes to the increased arterial stiffness of this condition. 3,4 The production of collagen in the vessel wall is likely regulated by a combination of mechanical forces and soluble growth factors. Of the latter, transforming growth factor-␤ (TGF-␤) is known to stimulate synthesis of collagen in vascular smooth muscle cells (SMCs), 5 whereas interferon-␥, fibroblast growth factor-2, and nitric oxide have been shown to decrease SMC collagen production.…”
mentioning
confidence: 99%
“…Hypertension is known to be associated with an increased synthesis of arterial elastin, collagen, and fibronectin. 21 -22 * 28 - 29 Cilazapril might have an effect not only on monocyte macrophages but also on noncellular elements in the intima.…”
mentioning
confidence: 99%